Measurement of the Impact of the 8 April 2024 Total Solar Eclipse on Surface Layer Turbulence and Boundary Layer Structure near Bloomington, Indiana - Sean C. C. Bailey; Christina N. Hisle; Tracy L. Knowles; James W. Morris; Ryan D. Nolin; Nicolas E. Pichette-Emmons; Suzanne Weaver Smith (Boundary-Layer Meteorology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Performance metrics for resilience of airport infrastructure - Robert Horton; Benjamin D. Trump; Joshua Trump; Hal S. Knowles; Igor Linkov; Pierce Jones; Greg Kiker (Transportation Research Part D: Transport and Environment, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Spatial variability in water strontium isotopes and trace metals from the Clarence River Basin, New South Wales, Australia - Lauren J. Stoot; Lee J. Baumgartner; Gavin L. Butler; Jason D. Thiem; Brett M. Knowles; Gregory S. Doran (Hydrobiologia, 2024)
Understanding fish movement in river systems is essential in identifying habitats which are important for species to perpetuate. Water chemistry, paired with fish otoliths, can be used to trace movements among different habitats, although a detailed understanding of spatial variation in water chemistry is first required. To obtain this knowledge, we analysed surface water collected from 59 sites throughout the Clarence River Basin, a coastal river basin in northern New South Wales, Australia. The primary objective was to quantify the spatial variation of trace metals and strontium isotope ratios ( 87 Sr: 86 Sr) for future and paired use with otolith microchemistry to track fish movement. Using ICP-OES, we identified that some trace metals, particularly strontium and barium as well as 87 Sr: 86 Sr ratios, varied spatially when analysing all water samples and revealed three distinct regions centring around the estuary, interior and outer regions. These differences were driven by variation in the underlying surface geology between the Clarence–Moreton Basin and the New England Block. Tidal influence also affected trace metals and 87 Sr: 86 Sr ratios throughout the estuarine area. We suggest that the level of differentiation identified in the current study has the potential to discriminate broad-scale fish movements among regions/habitats using otolith analysis, with fine scale movements best elucidated using complementary techniques.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Stony coral tissue loss disease: a review of emergence, impacts, etiology, diagnostics, and intervention - Erin Papke; Ashley Carreiro; Caroline Dennison; Jessica M. Deutsch; Lys M. Isma; Sonora S. Meiling; Ashley M. Rossin; Andrew C. Baker; Marilyn E. Brandt; Neha Garg; Daniel M. Holstein; Nikki Traylor-Knowles; et al. (Frontiers in Marine Science, 2024)
Stony coral tissue loss disease (SCTLD) is destructive and poses a significant threat to Caribbean coral reef ecosystems. Characterized by the acute loss of coral tissue, SCTLD has impacted over 22 stony coral species across the Caribbean region, leading to visible declines in reef health. Based on the duration, lethality, host range, and spread of this disease, SCTLD is considered the most devastating coral disease outbreak ever recorded. Researchers are actively investigating the cause and transmission of SCTLD, but the exact mechanisms, triggers, and etiological agent(s) remain elusive. If left unchecked, SCTLD could have profound implications for the health and resilience of coral reefs worldwide. To summarize what is known about this disease and identify potential knowledge gaps, this review provides a holistic overview of SCTLD research, including species susceptibility, disease transmission, ecological impacts, etiology, diagnostic tools, host defense mechanisms, and treatments. Additionally, future research avenues are highlighted, which are also relevant for other coral diseases. As SCTLD continues to spread, collaborative efforts are necessary to develop effective strategies for mitigating its impacts on critical coral reef ecosystems. These collaborative efforts need to include researchers from diverse backgrounds and underrepresented groups to provide additional perspectives for a disease that requires creative and urgent solutions.

Experiences of and support for black women in ecology, evolution, and marine science - Nikki Traylor-Knowles; Anamica Bedi de Silva; Anjali D. Boyd; Karlisa A. Callwood; Alexandra C. D. Davis; Giselle Hall; Victoria Moreno; Cinda P. Scott (Frontiers in Marine Science, 2023)
Systemic racism and sexism are well documented in ecology, evolution, and marine science. To combat this, institutions are making concerted efforts to recruit more diverse people by focusing on the recruitment of Black people. However, despite these initiatives, white supremacy culture still prevails. The retention of Black people in ecology, evolution, and marine science has not increased in the ways that were hoped for. This is particularly true for Black women, who struggle to find a safe working environment that values their contributions and allows them to openly celebrate their own culture and identity. In this perspective article, we discuss the challenges that Black women face every day, and the needs of Black women to thrive in ecology, evolution, and marine science. We have written this directly to Black women and provide information on not only our challenges, but our stories. However, readers of all identities are welcome to listen and examine their role in perpetuating systemic racism and sexism. Lastly, we discuss support mechanisms for navigating ecology, evolution, and marine science spaces so that Black women can thrive.

Ocean acidification influences the gene expression and physiology of two Caribbean bioeroding sponges - John T. Morris; Ian C. Enochs; Michael S. Studivan; Benjamin D. Young; Anderson Mayfield; Nash Soderberg; Nikki Traylor-Knowles; Graham Kolodziej; Derek Manzello (Frontiers in Marine Science, 2023)
Introduction Coral reef ecosystems are experiencing increased rates of carbonate dissolution due to losses in live coral cover coupled with the impacts of ocean acidification (OA) on coral reef calcifiers and bioeroders. While the stimulating effect of OA on bioerosion has been demonstrated experimentally, predominantly in the Pacific, the underlying physiological and molecular mechanisms behind the response are still poorly understood. Methods To address this, we subjected common zooxanthellate ( Cliona varians ) and azooxanthellate ( Pione lampa ) Caribbean sponges to pre-industrial (8.15 pH), present-day (8.05 pH), and two future OA scenarios (moderate OA, 7.85 pH; extreme OA, 7.75 pH) and evaluated their physiological and transcriptomic responses. Results The influence of OA on sponge bioerosion was nonlinear for both species, with the greatest total bioerosion and chemical dissolution rates found in the 7.85 pH treatment, then not increasing further under the more extreme 7.75 pH conditions. A trend towards reduced bioerosion rates in the 7.75 pH treatment occurred regardless of the presence of algal symbionts and suggests that the sponges may become physiologically impaired under prolonged OA exposure, resulting in diminished bioerosion potential. These findings were supported by the RNA-seq analysis, which revealed differentially expressed genes involved in a stress response to OA, in particular, suppressed metabolism. Discussion This may indicate that the sponges had reallocated energy resources towards more critical physiological needs in response to OA as a survival mechanism under stressful conditions. These data reveal that while the bioerosion rates of excavating sponges in Caribbean reef ecosystems may increase under moderate OA scenarios, this OA-stimulation may plateau or be lost at extreme end-of-century pH conditions, with implications for the dissolution and long-term persistence of reef habitat structures.

Bark beetle impacts on forest evapotranspiration and its partitioning - John F. Knowles; Nels R. Bjarke; Andrew M. Badger; Max Berkelhammer; Joel A. Biederman; Peter D. Blanken; Mario Bretfeld; Sean P. Burns; Brent E. Ewers; John M. Frank; Jeffrey A. Hicke; Leanne Lestak; et al. (Science of The Total Environment, 2023)

Electroconductive and mechano-competent PUCL@CNT nanohybrid scaffolds guiding neuronal specification of neural stem/progenitor cells - Yu-Meng Li; Kapil D. Patel; Yoon-Koo Han; Suk-Min Hong; Yu-Xuan Meng; Hae-Hyoung Lee; Jeong Hui Park; Jonathan C. Knowles; Jung Keun Hyun; Jung-Hwan Lee; Hae-Won Kim (Chemical Engineering Journal, 2023)

Echo Russet: A Russet Potato Variety with a High Yield of Marketable Tubers, High Processing Quality, and Few Tuber Defects - N. Baley; V. Sathuvalli; B. A. Charlton; C. C. Shock; S. Yilma; R. Qin; E. Feibert; M. I. Vales; R. G. Novy; J. L. Whitworth; C. Brown; D. A. Navarre; et al. (American Journal of Potato Research, 2023)

Comparative phylogeography in the genomic age: Opportunities and challenges - Angela McGaughran; Libby Liggins; Katharine A. Marske; Michael N Dawson; Lauren M. Schiebelhut; Shane D. Lavery; L. Lacey Knowles; Craig Moritz; Cynthia Riginos (Journal of Biogeography, 2022)
Aim We consider the opportunities and challenges comparative phylogeography (CP) faces in the genomic age to determine: (1) how we can maximise the potential of big CP analyses to advance biogeographic and macroevolutionary theory; and (2) what we can, and will struggle, to achieve using CP approaches in this era of genomics. Location World‐wide. Taxon All. Methods We review the literature to discuss the future of CP ‐ particularly examining CP insights enabled by genomics that may not be possible for single species and/or few molecular markers. We focus on how geography and species' natural histories interact to yield congruent and incongruent patterns of neutral and adaptive processes in the context of both historical and recent rapid evolution. We also consider how CP genomic data are being stored, accessed, and shared. Results With the widespread availability of genomic data, the shift from a single‐ to a multi‐locus perspective is resulting in detailed historical inferences and an improved statistical rigour in phylogeography. However, the time and effort required for collecting co‐distributed species and accruing species‐specific ecological knowledge continue to be limiting factors. Bioinformatic skills and user‐friendly analytical tools, alongside the computational infrastructure required for big data, can also be limiting. Main conclusions Over the last ~35 years, there has been much progress in understanding how intraspecific genetic variation is geographically distributed. The next major steps in CP will be to incorporate evolutionary processes and community perspectives to account for patterns and responses among co‐distributed species and across temporal scales, including those related to anthropogenic change. However, the full potential of CP will only be realised if we employ robust study designs within a sound comparative framework. We advocate that phylogeographers adopt such consistent approaches to enhance future comparisons to present‐day findings.

Advances in coral immunity ‘omics in response to disease outbreaks - Nikki Traylor-Knowles; Andrew C. Baker; Kelsey M. Beavers; Neha Garg; Jeffrey R. Guyon; Aine Hawthorn; Nicholas J. MacKnight; Mónica Medina; Laura D. Mydlarz; Esther C. Peters; Julia Marie Stewart; Michael S. Studivan; et al. (Frontiers in Marine Science, 2022)
Coral disease has progressively become one of the most pressing issues affecting coral reef survival. In the last 50 years, several reefs throughout the Caribbean have been severely impacted by increased frequency and intensity of disease outbreaks leading to coral death. A recent example of this is stony coral tissue loss disease which has quickly spread throughout the Caribbean, devastating coral reef ecosystems. Emerging from these disease outbreaks has been a coordinated research response that often integrates ‘omics techniques to better understand the coral immune system. ‘Omics techniques encompass a wide range of technologies used to identify large scale gene, DNA, metabolite, and protein expression. In this review, we discuss what is known about coral immunity and coral disease from an ‘omics perspective. We reflect on the development of biomarkers and discuss ways in which coral disease experiments to test immunity can be improved. Lastly, we consider how existing data can be better leveraged to combat future coral disease outbreaks.

Direct 14C dating of equine products preserved in archaeological pottery vessels from Botai and Bestamak, Kazakhstan - Emmanuelle Casanova; Timothy D. J. Knowles; Alan K. Outram; Natalie A. Stear; Mélanie Roffet-Salque; Viktor Zaibert; Andrey Logvin; Irina Shevnina; Richard P. Evershed (Archaeological and Anthropological Sciences, 2022)
Direct and accurate radiocarbon dating of lipid residues preserved in ceramics is a recently established method that allows direct dating of specific food products and their inception in human subsistence strategies. The method targets individual fatty acids originating from animal fats such as ruminant dairy, ruminant adipose, non-ruminant adipose and aquatic fats. Horse lipid residues found in Central Asian pottery vessels are also directly dateable using this new method. Here we present the identification of equine lipid residues preserved in two pottery assemblages from the Neolithic and Eneolithic in Kazakhstan and their direct 14 C dating. The site of Botai, previously radiocarbon-dated to the 4th millennium BC, was used as a reference to evaluate the dates obtained directly on horse lipids. The direct dating of equine products extracted from Botai potsherds are shown to be compatible with previous 14 C dates at the site. The site of Bestamak, lacking previous 14 C measurements, had been relatively dated to the Neolithic based on pottery typologies. The direct dating of equine residues made it possible to anchor the pottery assemblage of Bestamak in the 6th millennium BC confirming their Neolithic attribution. These findings demonstrate the potential for dating horse products through a compound-specific approach, while highlighting challenges in 14 C dating individual fatty acids from lipid extracts in which their abundances differ substantially.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Vanguard Russet: A Fresh Market Potato Cultivar with Medium-Early Maturity and Long Dormancy - M. I. Vales; D. C. Scheuring; J. W. Koym; D. G. Holm; S. Y. C. Essah; R. G. Wilson; J. K. Sidhu; R. G. Novy; J. L. Whitworth; J. C. Stark; R. R. Spear; V. Sathuvalli; et al. (American Journal of Potato Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Gene Expression Response to Stony Coral Tissue Loss Disease Transmission in M. cavernosa and O. faveolata From Florida - Nikki Traylor-Knowles; Michael T. Connelly; Benjamin D. Young; Katherine Eaton; Erinn M. Muller; Valerie J. Paul; Blake Ushijima; Allyson DeMerlis; Melissa K. Drown; Ashley Goncalves; Nicholas Kron; Grace A. Snyder; et al. (Frontiers in Marine Science, 2021)
Since 2014, corals within Florida’s Coral Reef have been dying at an unprecedented rate due to stony coral tissue loss disease (SCTLD). Here we describe the transcriptomic outcomes of three different SCTLD transmission experiments performed at the Smithsonian Marine Station and Mote Marine Laboratory between 2019 and 2020 on the corals Orbicella faveolata and Montastraea cavernosa. Overall, diseased O. faveolata had 2194 differentially expressed genes (DEGs) compared with healthy colonies, whereas diseased M. cavernosa had 582 DEGs compared with healthy colonies. Many significant DEGs were implicated in immunity, extracellular matrix rearrangement, and apoptosis. These included, but not limited to, peroxidases, collagens, Bax-like, fibrinogen-like, protein tyrosine kinase, and transforming growth factor beta. A gene module was identified that was significantly correlated to disease transmission. This module possessed many apoptosis and immune genes with high module membership indicating that a complex apoptosis and immune response is occurring in corals during SCTLD transmission. Overall, we found that O. faveolata and M. cavernosa exhibit an immune, apoptosis, and tissue rearrangement response to SCTLD. We propose that future studies should focus on examining early time points of infection, before the presence of lesions, to understand the activating mechanisms involved in SCTLD.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Montane forest productivity across a semiarid climatic gradient - John F. Knowles; Russell L. Scott; Joel A. Biederman; Peter D. Blanken; Sean P. Burns; Sabina Dore; Thomas E. Kolb; Marcy E. Litvak; Greg A. Barron‐Gafford (Global Change Biology, 2020)
High‐elevation montane forests are disproportionately important to carbon sequestration in semiarid climates where low elevations are dry and characterized by low carbon density ecosystems. However, these ecosystems are increasingly threatened by climate change with seasonal implications for photosynthesis and forest growth. As a result, we leveraged eddy covariance data from six evergreen conifer forest sites in the semiarid western United States to extrapolate the status of carbon sequestration within a framework of projected warming and drying. At colder locations, the seasonal evolution of gross primary productivity (GPP) was characterized by a single broad maximum during the summer that corresponded to snow melt‐derived moisture and a transition from winter dormancy to spring activity. Conversely, winter dormancy was transient at warmer locations, and GPP was responsive to both winter and summer precipitation such that two distinct GPP maxima were separated by a period of foresummer drought. This resulted in a predictable sequence of primary limiting factors to GPP beginning with air temperature in winter and proceeding to moisture and leaf area during the summer. Due to counteracting winter (positive) and summer (negative) GPP responses to warming, leaf area index and moisture availability were the best predictors of annual GPP differences across sites. Overall, mean annual GPP was greatest at the warmest site due to persistent vegetation photosynthetic activity throughout the winter. These results indicate that the trajectory of this region's carbon sequestration will be sensitive to reduced or delayed summer precipitation, especially if coupled to snow drought and earlier soil moisture recession, but summer precipitation changes remain highly uncertain. Given the demonstrated potential for seasonally offsetting responses to warming, we project that decadal semiarid montane forest carbon sequestration will remain relatively stable in the absence of severe disturbance.

RAD-Seq Analysis and in situ Monitoring of Nassau Grouper Reveal Fine-Scale Population Structure and Origins of Aggregating Fish - Krista D. Sherman; Josephine R. Paris; Robert Andrew King; Karen A. Moore; Craig P. Dahlgren; Lindy C. Knowles; Kristine Stump; Charles R. Tyler; Jamie R. Stevens (Frontiers in Marine Science, 2020)

Increasing the Production Efficiency of Potato with Plant Growth Retardants - Graham D. Ellis; Lisa O. Knowles; N. Richard Knowles (American Journal of Potato Research, 2020)

The age of ambergris - Steven John Rowland; Paul Andrew Sutton; Timothy D. J. Knowles (Natural Product Research, 2019)

Biochemical diversity of glycosphingolipid biosynthesis as a driver of Coccolithovirus competitive ecology - Jozef I. Nissimov; David Talmy; Liti Haramaty; Helen F. Fredricks; Ehud Zelzion; Ben Knowles; A. Murat Eren; Rebecca Vandzura; Christien P. Laber; Brittany M. Schieler; Christopher T. Johns; Kuldeep D. More; et al. (Environmental Microbiology, 2019)
Summary Coccolithoviruses (EhVs) are large, double‐stranded DNA‐containing viruses that infect the single‐celled, marine coccolithophore Emiliania huxleyi . Given the cosmopolitan nature and global importance of E. huxleyi as a bloom‐forming, calcifying, photoautotroph, E. huxleyi –EhV interactions play a key role in oceanic carbon biogeochemistry. Virally‐encoded glycosphingolipids (vGSLs) are virulence factors that are produced by the activity of virus‐encoded serine palmitoyltransferase (SPT). Here, we characterize the dynamics, diversity and catalytic production of vGSLs in an array of EhV strains in relation to their SPT sequence composition and explore the hypothesis that they are a determinant of infectivity and host demise. vGSL production and diversity was positively correlated with increased virulence, virus replication rate and lytic infection dynamics in laboratory experiments, but they do not explain the success of less‐virulent EhVs in natural EhV communities. The majority of EhV‐derived SPT amplicon sequences associated with infected cells in the North Atlantic derived from slower infecting, less virulent EhVs. Our lab‐, field‐ and mathematical model‐based data and simulations support ecological scenarios whereby slow‐infecting, less‐virulent EhVs successfully compete in North Atlantic populations of E. huxleyi , through either the preferential removal of fast‐infecting, virulent EhVs during active infection or by having access to a broader host range.

TerraRossa: A Mid-Season Specialty Potato with Red Flesh and Skin and Resistance to Common Scab and Golden Cyst Nematode - C. C. Shock; C. R. Brown; V. Sathuvalli; B. A. Charlton; S. Yilma; D. C. Hane; R. Quick; K. A. Rykbost; S. R. James; A. R. Mosley; E. B. G. Feibert; J. L. Whitworth; et al. (American Journal of Potato Research, 2018)

Reveille Russet: An Early, Widely Adapted, High-Count-Carton Russet for the Fresh Market - J. C. Miller; D. C. Scheuring; J. W. Koym; D. G. Holm; J. J. Pavek; R. G. Novy; J. L. Whitworth; J. C. Stark; B. A. Charlton; S. Yilma; N. R. Knowles; M. J. Pavek; et al. (American Journal of Potato Research, 2018)

Sage Russet: a New High Yielding Russet Potato Variety with Cold-Sweetening Resistance, High Vitamin C and Protein Contents and Excellent Fresh Pack and Processing Potential - S. Yilma; B. A. Charlton; C. C. Shock; D. C. Hane; S. R. James; A. R. Mosley; K. A. Rykbost; E. B. G. Feibert; N. R. Knowles; M. J. Pavek; J. C. Stark; R. G. Novy; et al. (American Journal of Potato Research, 2017)

Breaking out of biogeographical modules: range expansion and taxon cycles in the hyperdiverse ant genus Pheidole - Evan P. Economo; Eli M. Sarnat; Milan Janda; Ronald Clouse; Pavel B. Klimov; Georg Fischer; Benjamin D. Blanchard; Lizette N. Ramirez; Alan N. Andersen; Maia Berman; Benoit Guénard; Andrea Lucky; et al. (Journal of Biogeography, 2015)
Aim We sought to reconstruct the biogeographical structure and dynamics of a hyperdiverse ant genus, Pheidole, and to test several predictions of the taxon cycle hypothesis. Using large datasets on Pheidole geographical distributions and phylogeny, we (1) inferred patterns of biogeographical modularity (clusters of areas with similar faunal composition), (2) tested whether species in open habitats are more likely to be expanding their range beyond module boundaries, and (3) tested whether there is a bias of lineage flow from high‐ to low‐diversity areas. Location The Old World. Methods We compiled and jointly analysed a comprehensive database of Pheidole geographical distributions, the ecological affinities of different species, and a multilocus phylogeny of the Old World radiation. We used network modularity methods to infer biogeographical structure in the genus and comparative methods to evaluate the hypotheses. Results The network analysis identified eight biogeographical modules, and a suite of species with anomalous ranges that are statistically more likely to occur in open habitat, supporting the hypothesis that open habitats promote range expansion. Phylogenetic analysis shows evidence for a cascade pattern of colonization from Asia to New Guinea to the Pacific, but no ‘upstream’ colonization in the reverse direction. Main conclusions The distributions of Pheidole lineages in the Old World are highly modular, with modules generally corresponding to biogeographical regions inferred in other groups of organisms. However, some lineages have expanded their ranges across module boundaries, and these species are more likely to be adapted to open habitats rather than interior forest. In addition, there is a cascade pattern of dispersal from higher to lower diversity areas during these range expansions. Our findings are consistent with the taxon cycle hypothesis, although they do not rule out alternative interpretations.

ATTX961014-1R/Y a.k.a. Sierra RoseTM: A Red-Skin, Yellow-Flesh Potato Cultivar for the Specialty/Gourmet Market - J. C. Miller; D. C. Scheuring; J. W. Koym; D. G. Holm; J. J. Pavek; R. G. Novy; J. L. Whitworth; J. C. Stark; B. A. Charlton; S. Yilma; N. R. Knowles; M. J. Pavek; et al. (American Journal of Potato Research, 2015)

Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2015) - M. J. Adams; E. J. Lefkowitz; A. M. Q. King; D. H. Bamford; M. Breitbart; A. J. Davison; S. A. Ghabrial; A. E. Gorbalenya; N. J. Knowles; P. Krell; R. Lavigne; D. Prangishvili; et al. (Archives of Virology, 2015)

Heritable changes in regional cortical thickness with age - Francois Chouinard-Decorte; D. Reese McKay; Andrew Reid; Budhachandra Khundrakpam; Lu Zhao; Sherif Karama; Pierre Rioux; Emma Sprooten; Emma Knowles; Jack W. Kent; Joanne E. Curran; Harald H. H. Göring; et al. (Brain Imaging and Behavior, 2014)

Influence of age, sex and genetic factors on the human brain - D. Reese McKay; Emma E. M. Knowles; Anderson A. M. Winkler; Emma Sprooten; Peter Kochunov; Rene L. Olvera; Joanne E. Curran; Jack W. Kent; Melanie A. Carless; Harald H. H. Göring; Thomas D. Dyer; Ravi Duggirala; et al. (Brain Imaging and Behavior, 2014)

Purple Pelisse: A Specialty ‘Fingerling’ Potato with Purple Skin and Flesh and Medium Specific Gravity - M. I. Vales; C. R. Brown; S. Yilma; D. C. Hane; S. R. James; C. C. Shock; B. A. Charlton; E. Karaagac; A. R. Mosley; D. Culp; E. Feibert; J. C. Stark; et al. (American Journal of Potato Research, 2012)

Effects of vicariant barriers, habitat stability, population isolation and environmental features on species divergence in the south‐western Australian coastal reptile community - D. L. EDWARDS; J. S. KEOGH; L. L. KNOWLES (Molecular Ecology, 2012)
Identifying explicit hypotheses regarding the factors determining genetic structuring within species can be difficult, especially in species distributed in historically dynamic regions. To contend with these challenges, we use a framework that combines species distribution models, environmental data and multi‐locus genetic data to generate and explore phylogeographic hypotheses for reptile species occupying the coastal sand‐dune and sand‐plain habitats of the south‐western Australian biodiversity hotspot, a community which has both a high diversity of endemics and has varied dramatically in spatial extent over time. We use hierarchical amova , summary statistic and distance‐based analyses to explicitly test specific phylogeographic hypotheses. Namely, we test if biogeographic vicariance across barriers, habitat stability, population isolation along a linear habitat or fragmentation across different environments can explain genetic divergence within five co‐distributed squamate reptile species. Our results show that patterns of genetic variation reflect complex and species‐specific interactions related to the spatial distribution of habitats present currently and during repeated glacial minima, as opposed to being associated with historical factors such as habitat stability between glacial and inter‐glacial periods or vicariant barriers. We suggest that the large impact of habitat characteristics over time (i.e. relative levels of habitat connectivity, climatic gradients and spatial heterogeneity of soil types) reflects the ecological restrictions of the sand‐dune and sand‐plain reptile communities and may explain the lack of concordance across taxa. The study demonstrates the general utility of the approach for assemblage‐level, as well as single species, phylogeographic study, including its usefulness for exploring biologically informed hypotheses about what factors have influenced patterns of genetic variation.

Owyhee Russet: A Variety with High Yields of U.S. No. 1 Tubers, Excellent Processing Quality, and Moderate Resistance to Fusarium Dry Rot (Fusarium solani var. coeruleum) - S. Yilma; M. I. Vales; B. A. Charlton; D. C. Hane; S. R. James; C. C. Shock; A. R. Mosley; D. Culp; E. Feibert; L. Leroux; E. Karaagac; N. R. Knowles; et al. (American Journal of Potato Research, 2012)

Palisade Russet: A Late Blight Resistant Potato Cultivar Having a Low Incidence of Sugar Ends and High Specific Gravity - R. G. Novy; J. L. Whitworth; J. C. Stark; B. A. Charlton; S. Yilma; N. R. Knowles; M. J. Pavek; T. L. Brandt; S. Gupta; N. Olsen; M. Thornton; C. R. Brown; et al. (American Journal of Potato Research, 2012)

Comparative sequence analysis of representative foot-and-mouth disease virus genomes from Southeast Asia - Nor Faizah Abdul-Hamid; Müge Fırat-Saraç; Alan D. Radford; Nick J. Knowles; Donald P. King (Virus Genes, 2011)

Classic Russet: A Potato Cultivar with Excellent Fresh Market Characteristics and High Yields of U.S. No. 1 Tubers Suitable for Early Harvest or Full-Season Production - Jeffrey C. Stark; Richard G. Novy; Jonathan L. Whitworth; N. R. Knowles; Mark J. Pavek; Steve L. Love; M. I. Vales; S. R. James; D. C. Hane; C. R. Brown; B. A. Charlton; Dennis L. Corsini; et al. (American Journal of Potato Research, 2010)

Interpreting seawater temperature range using oxygen isotopes and zooid size variation in Pentapora foliacea (Bryozoa) - T. Knowles; M. J. Leng; M. Williams; P. D. Taylor; H. J. Sloane; B. Okamura (Marine Biology, 2010)

Human ES cell lines—introduction - Peter W. Andrews; Nissim Benvenisty; Barbara B. Knowles; Ronald D. G. McKay; Steve K. W. Oh; Martin F. Pera; Janet Rossant; Glyn N. Stacey (In Vitro Cellular & Developmental Biology - Animal, 2010)

Comparison of defined culture systems for feeder cell free propagation of human embryonic stem cells - Veronika Akopian; Peter W. Andrews; Stephen Beil; Nissim Benvenisty; Jennifer Brehm; Megan Christie; Angela Ford; Victoria Fox; Paul J. Gokhale; Lyn Healy; Frida Holm; Outi Hovatta; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Phosphatidylinositol 3-kinase (PI3K) pathway activation in bladder cancer - Margaret A. Knowles; Fiona M. Platt; Rebecca L. Ross; Carolyn D. Hurst (Cancer and Metastasis Reviews, 2009)

Highland Russet: A Full Season, Processing Variety with High Yields of Uniform U.S. No. 1 Tubers - J. C. Stark; R. G. Novy; J. L. Whitworth; S. L. Love; D. L. Corsini; J. J. Pavek; M. I. Vales; S. R. James; D. C. Hane; B. A. Charlton; C. R. Brown; N. R. Knowles; et al. (American Journal of Potato Research, 2009)

Aquaporin expression in the human intervertebral disc - S. M. Richardson; R. Knowles; D. Marples; J. A. Hoyland; A. Mobasheri (Journal of Molecular Histology, 2008)

Premier Russet: A Dual-Purpose, Potato Cultivar with Significant Resistance to Low Temperature Sweetening During Long-Term Storage - R. G. Novy; J. L. Whitworth; J. C. Stark; S. L. Love; D. L. Corsini; J. J. Pavek; M. I. Vales; S. R. James; D. C. Hane; C. C. Shock; B. A. Charlton; C. R. Brown; et al. (American Journal of Potato Research, 2008)

Willamette: A Chipping Cultivar with High Yield and Specific Gravity, Low Incidence of Hollow Heart and Brown Center, and Suitability for Fresh-Market Usage - A. R. Mosley; S. Yilma; D. C. Hane; S. R. James; K. A. Rykbost; C. C. Shock; S. L. Love; D. L. Corsini; J. J. Pavek; R. E. Thornton; B. A. Charlton; E. P. Eldredge; et al. (American Journal of Potato Research, 2008)

Blazer russet: An early to Mid-Season potato cultivar with high U.S. no. 1 yields and good processing and culinary qualities - J. C. Stark; R. G. Novy; S. L. Love; J. L. Whitworth; D. L. Corsini; J. J. Pavek; A. R. Mosley; M. J. Pavek; N. R. Knowles; R. E. Thornton; S. R. James; D. C. Hane; et al. (American Journal of Potato Research, 2007)

GemStar russet: A potato variety with high yield, good culinary quality, excellent fresh market appearance, and resistance to common scab - S. L. Love; R. G. Novy; J. Whitworth; D. L. Corsini; J. J. Pavek; A. R. Mosley; M. J. Pavek; N. R. Knowles; C. R. Brown; S. R. James; D. C. Hane; J. C. Miller (American Journal of Potato Research, 2006)

Western russet: A new potato variety with excellent fresh market and frozen-fried processing quality and field resistance to common scab and PVYo - S. L. Love; R. G. Novy; J. Whitworth; D. L. Corsini; J. J. Pavek; A. R. Mosley; M. J. Pavek; N. R. Knowles; C. R. Brown; S. R. James; D. C. Hane (American Journal of Potato Research, 2006)

Defender: A high-yielding, processing potato cultivar with foliar and tuber resistance to late blight - R. G. Novy; S. L. Love; D. L. Corsini; J. J. Pavek; J. L. Whitworth; A. R. Mosley; S. R. James; D. C. Hane; C. C. Shock; K. A. Rykbost; C. R. Brown; R. E. Thornton; et al. (American Journal of Potato Research, 2006)

Summit Russet: A new russet potato variety with good fresh market and frozen processing qualities - S. L. Love; R. Novy; J. Whitworth; D. L. Corsini; J. J. Pavek; A. R. Mosley; R. E. Thornton; N. R. Knowles; S. R. James; D. C. Hane (American Journal of Potato Research, 2005)

Molecular analysis indicates gene flow among populations of Paralvinella pandorae Desbruyères and Laubier 1986 (Alvinellidae, Terebellida), a polychaete annelid endemic to hydrothermal vents of the northeast Pacific - James D. Knowles; Emily Wenink; Nancy Schult; Verena Tunnicliffe; Damhnait McHugh (Marine Ecology, 2005)
The polychaete annelid Paralvinella pandorae Desbruyères and Laubier 1986 is endemic to hydrothermal vents in the northeast Pacific, and is found at almost all vents sites along the 500‐km long Juan de Fuca ridge (JdF) system. The sperm morphology of P. pandorae indicates that fertilization occurs internally or in the worm's tube, and the maximum observed oocyte size of 215 μ m suggests that a dispersive larval phase is short or non‐existent. Size frequency analyses of populations of P. pandorae suggest continuous or semi‐continuous recruitment of juveniles. Given our limited knowledge of the species’ life history, we predicted that populations of P. pandorae would exhibit a decline in genetic similarity with increasing distance among populations along the JdF. While our attempts to use amplified fragment length polymorphisms to test this prediction were not successful, our analysis of cytochrome oxidase I gene sequences provided insights into the phylogeography of the species. For 31 individuals from five sites along the JdF there is little sequence variation among individuals and no phylogeographic pattern among haplotypes from populations separated by distances of up to 210 km. These results indicate that gene flow occurs among all sites in the analyses, i.e. despite the very limited dispersal potential inferred from life history characteristics of this worm, there is no evidence for isolation‐by‐distance across the geographical scale of the study. Demersal larvae dispersed by near‐bottom currents might explain the gene flow among sites, as well as the establishment of populations of P. pandorae at new vents within a year.

Contact Chemosensory Cues in Egg Bundles Elicit Male–Male Agonistic Conflicts in the Squid Loligo pealeii - Kendra C. Buresch; Jean G. Boal; Jamie Knowles; Jennifer Debose; Amy Nichols; Ali Erwin; Sherry D. Painter; Gregg T. Nagle; Roger T. Hanlon (Journal of Chemical Ecology, 2003)

Seeing is Believing: The Role of Field Days and Tours in Precision Agriculture Education - R. W. Heiniger; J. L. Havlin; D. A. Crouse; C. Kvien; T. Knowles (Precision Agriculture, 2002)

Genetic heterogeneity of SAT-1 type foot-and-mouth disease viruses in southern Africa - A. D. S. Bastos; D. T. Haydon; R. Forsberg; N. J. Knowles; E. C. Anderson; R. G. Bengis; L. H. Nel; G. R. Thomson (Archives of Virology, 2001)

Gene flow on the ice: genetic differentiation among Adélie penguin colonies around Antarctica - Amy D. Roeder; Richelle K. Marshall; Amanda J. Mitchelson; Thungar Visagathilagar; Peter A. Ritchie; Donald R. Love; Trevor J. Pakai; Helen C. McPartlan; Neil D. Murray; Nick A. Robinson; Knowles R. Kerry; David M. Lambert (Molecular Ecology, 2001)
Each summer Adélie penguins breed in large disjunct colonies on ice‐free areas around the Antarctic continent. Comprising > 10 million birds, this species represents a dominant feature of the Antarctic ecosystem. The patchy distribution within a large geographical range, natal philopatry and a probable history of refugia, suggest that this species is likely to exhibit significant genetic differentiation within and among colonies. We present data from seven microsatellite DNA loci for 442 individuals from 13 locations around the Antarctic continent. With the exception of one locus, there was no significant genic or genotypic heterogeneity across populations. Pairwise F ST values were low with no value > 0.02. When all colonies were compared in a single analysis, the overall F ST value was 0.0007. Moreover, assignment tests were relatively ineffective at correctly placing individuals into their respective collection sites. These data reveal a lack of genetic differentiation between Adélie penguin colonies around the Antarctic continent, despite substantial levels of genetic variation. We consider this homogeneity in terms of the dispersal of individuals among colonies and the size of breeding groups and discuss our results in terms of the glacial history of Antarctica.

Urban ecology as an interdisciplinary field: differences in the use of “urban” between the social and natural sciences - N. E. Mcintyre; K. Knowles-Yánez; D. Hope (Urban Ecosystems, 2000)

Phylogenetic analysis of European encephalomyocarditis viruses: comparison of two genomic regions - F. Koenen; H. Vanderhallen; N. D. Dickinson; N. J. Knowles (Archives of Virology, 1999)

Relationships of chestnut species and New Zealand chestnut selections using morpho-nut characters - Nnadozie C. Oraguzie; David L. McNeil; David J. Klinac; Ray D. Knowles; J. Richard Sedcole (Euphytica, 1998)

Persistence and toxicity of alkyllead salts to anaerobic nitrogen transformations in soil - Jean Simon Blais; Carl A. Doige; William D. Marshall; Roger Knowles (Archives of Environmental Contamination and Toxicology, 1990)

Characterization of a new polyomavirus (Polyomavirus papionis-2) isolated from baboon kidney cell cultures - Sylvia D. Gardner; Wendy A. Knowles; J. F. Hand; A. A. Porter (Archives of Virology, 1989)

Immunization of foxes against rabies with a vaccinia recombinant virus expressing the rabies glycoprotein - N. D. Tolson; K. M. Charlton; G. A. Casey; M. K. Knowles; C. E. Rupprecht; K. F. Lawson; J. B. Campbell (Archives of Virology, 1988)

Plant growth response from aged potato seed-tubers as affected by meristem selection and NAA - N. Richard Knowles; W. M. Iritani; L. D. Weller (American Journal of Potato Research, 1985)

Factors influencing incidence of internal brown spot in Russet Burbank potatoes - W. M. Iritani; L. D. Weller; N. R. Knowles (American Journal of Potato Research, 1984)

Relationships between stem number, tuber set and yield of Russet Burbank potatoes - W. M. Iritani; L. D. Weiler; N. R. Knowles (American Journal of Potato Research, 1983)

Susceptibility of potatoes to bacterial rot and weight loss as a function of wound-healing interval and temperature - N. R. Knowles; W. M. Iritani; L. D. Weiler; D. C. Gross (American Journal of Potato Research, 1982)

A comparison of cervical cytomegalovirus (CMV) excretion in gynaecological patients and post-partum women - Wendy A. Knowles; Sylvia D. Gardner; H. Fox (Archives of Virology, 1982)

Intermediary metabolism of carbon compounds by nitrifying bacteria - W. Wallace; S. E. Knowles; D. J. D. Nicholas (Archives of Microbiology, 1970)